Optimization of The Use of The I-24/7 Network System by Bagkominter to Overcome Transnational Crime The Realization of Modern Police in The Era 4.0 - Nufani Puspita Sari; Basir - S; Lin - Yola (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Indonesia has committed and is ready to implement Industry 4.0 to build a globally competitive manufacturing industry. Polri participates in supporting Indonesia towards the 4.0 era. Through precision towards modern policing, it is hoped that all police officers must be able to make good use of digital technology and continuously improve their capabilities in its implementation. The International Communications Section or abbreviated as Bagkominter has the main task of organizing and developing an information exchange system in efforts to prevent and eradicate international/transnational crimes through the INTERPOL network (I-24/7), ASEANAPOL and other information facilities; as well as collecting information and data processing. Based on the explanation described above, the problem will arise "How to optimize the use of the I-24/7 Network System by the Kominter Unit to Overcome Transnational Crime in the Context of Realizing Modern Police in the 4.0 era?". From these main problems, the author also creates problems, including: "How do you optimize human resources, budget support, infrastructure and methods in using the I-24/7 network system by Bagkominter?" The approach used in this thesis is qualitative by using descriptive analysis method. Data collection techniques using interviews. Data analysis techniques using data reduction. data presentation, and drawing conclusions. Based on the research results, it can be explained that there is still a limited number of personnel and personnel competence, the operating budget for the I-24/7 network system is still inadequate, the facilities and infrastructure owned are still inadequate and the methods for dealing with transnational crimes are still not running optimally